Project Forward: A Population-Based Cohort Among Young Adult Survivors of Childhood Cancers. Issue 5 (17th July 2021) - Milam, Joel; Freyer, David R; Miller, Kimberly A; Tobin, Jessica; Wojcik, Katherine Y; Ramirez, Cynthia N; Ritt-Olson, Anamara; Thomas, Stefanie M; Baezconde-Garbanati, Lourdes; Cousineau, Michael; Modjeski, Denise; Gupta, Sapna; et al.
Abstract: Background: Childhood cancer survivors (CCS) face increased risk of morbidity and are recommended to receive lifelong cancer-related follow-up care. Identifying factors associated with follow-up care can inform efforts to support the long-term health of CCS. Methods: Eligible CCS (diagnosed between 1996 and 2010) identified through the Los Angeles County Cancer Surveillance Program responded to a self-report survey that assessed demographic, clinical, health-care engagement, and psychosocial risk and protective factors of recent (prior 2 years) cancer-related follow-up care. Weighted multivariable logistic regression was conducted to identify correlates of care. All statistical tests were 2-sided. Results: The overall response rate was 44.9%, with an analytical sample of n = 1106 (54.2% Hispanic; mean [SD] ages at survey, diagnosis, and years since diagnosis were 26.2 [4.9], 11.6 [5.4], and 14.5 [4.4] years, respectively). Fifty-seven percent reported a recent cancer-related visit, with lower rates reported among older survivors. Having insurance, more late effects, receipt of a written treatment summary, discussing long-term care needs with treating physician, knowledge of the need for long-term care, having a regular source of care, and higher health-care self-efficacy were statistically significantly associated with greater odds of recent follow-up care, whereas older age, Hispanic or Other ethnicity (vs non-Hispanic White), and years since diagnosis were associated with lower odds of recent care (all Ps < .05). Conclusions: Age and ethnic disparities are observed in receipt of follow-up care among young adult CCS. Potential intervention targets include comprehensive, ongoing patient education; provision of written treatment summaries; and culturally tailored support to ensure equitable access to and the utilization of care.